2015
DOI: 10.1080/17586801.2015.1074058
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of print in books for preschool children

Abstract: Children begin to learn about the characteristics of print well before formal literacy instruction begins. Reading to children can expose them to print and help them learn about its characteristics. This may be especially true if the print is visually salient, for studies suggest that prereaders pay more attention to such print than to print that is visually less salient. To shed light on the characteristics of the print that US children see in books, especially those characteristics that may contribute to vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These findings are supported by theories regarding the characteristics of learners since they prefer colorful material in video form to printed material especially if it is not colorful and only filled with text (Jakovljević et al, 2021;Stern-Ellran, Zilcha-Mano, Sebba, & Levit Binnun, 2016;Treiman, 2016). In addition, colorful media can also help young learners memorize better (Diachenko, Kalishchuk, Zhylin, Kyyko, & Volkova, 2022).…”
Section: Analyzesupporting
confidence: 58%
“…These findings are supported by theories regarding the characteristics of learners since they prefer colorful material in video form to printed material especially if it is not colorful and only filled with text (Jakovljević et al, 2021;Stern-Ellran, Zilcha-Mano, Sebba, & Levit Binnun, 2016;Treiman, 2016). In addition, colorful media can also help young learners memorize better (Diachenko, Kalishchuk, Zhylin, Kyyko, & Volkova, 2022).…”
Section: Analyzesupporting
confidence: 58%
“…It is not known whether shapes, consistencies, weights, and colors of the foreign bodies are effective factors for children's selection of the foreign bodies. However, various studies have indicated that children who start schooling are more interested in colored books which contribute to their enthusiasm to learn [23][24][25] . In the present study, colors of the foreign bodies inserted into the nasal cavities were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The second part is the design that concentrates on Color, Illustration, font, and style (Treiman, Rosales, & Kessler, 2016;Gönen et al, 2014). The illustration with the color has evocative artistic elements, and the color suggests certain feelings (Giorgis, 1999).…”
Section: Discussionmentioning
confidence: 99%